1999
DOI: 10.1302/0301-620x.81b5.9352
|View full text |Cite
|
Sign up to set email alerts
|

Detailed analysis of proprioception in normal and ACL-deficient knees

Abstract: We assessed proprioception using threshold levels for the perception of knee movement at slow angular velocities (0.1 degrees/s to 0.85 degrees/s) in 20 patients with unilateral tears of the anterior cruciate ligament (ACL) and 15 age-related control subjects. Failure to detect movement was also analysed. The threshold levels of detection did not differ between the damaged and undamaged knees in the patients or between the patients and the control group. Failure to appreciate movement, however, was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 15 publications
3
29
0
3
Order By: Relevance
“…In our study, proprioceptive deficits in both the uninjured and injured knees of ACL-injured patients were observed; this finding has been reported previously in the literature [6,26,28,30]. Roberts et al suggested that aberrant afferent information from the receptors of injured limb might also affect contralateral limb's muscle response [30].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, proprioceptive deficits in both the uninjured and injured knees of ACL-injured patients were observed; this finding has been reported previously in the literature [6,26,28,30]. Roberts et al suggested that aberrant afferent information from the receptors of injured limb might also affect contralateral limb's muscle response [30].…”
Section: Discussionsupporting
confidence: 89%
“…It seems that there are significant impacts on the detection of a bilateral proprioception deficit; results may vary depending on the external or internal controls used and the proprioceptive tests chosen. It has been reported that bilateral defects may follow a unilateral rupture and contralateral knee may not serve as a reliable control [6,10,26,28,30]. In our study we have established the external control group as well, and bilateral defects were detected in the injured group.…”
Section: Discussionmentioning
confidence: 70%
“…The anterior cruciate ligament (ACL) has documented proprioceptive function [26], and deficiency is known to cause walking difficulty especially when going downhill [18,27]. So the measurement of this task appears appropriate to determine whether functional deficits or advantages exist between procedures that sacrifice or preserve the ACL [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to instability secondary to ligament injury, other factors hastening progression of osteoarthritis include repetitive impingement between the ACL and a narrow intercondylar notch, especially in the presence of intercondylar osteophytes [22,23]. The presence of a lateral thrust during the stance phase of gait in patients with a varus deformity may also lead to attenuation and stretching of the lateral stabilizing structures, ultimately causing an ACL deficiency [14,24,25].…”
Section: Discussionmentioning
confidence: 99%